2017
DOI: 10.11118/actaun201765051607
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Tractor Tires Load on the Ground Loading Pressure

Abstract: The contribution, based on the experimental measurement, analyses the issue of a specific pad loading pressure in relation to radial wheel load and tire inflation. Tile inflation in terms of allowed radial load, which we wish to be high as far as possible in terms of the power transmission from the wheels to the ground is important for the field tensile works, on the other hand, the pressure in the tire is closely related to the contact area and ground loading pressure. The obtained results show the following:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
2
2
0
1
Order By: Relevance
“…Experimental studies of changes in the soil response from changes in the traction load on the hook of a wheeled tractor (Polcar et al, 2017) showed that with the traction resistance of the working tool in the range from 55 kPa to 70 kPa, there is a decrease in the pressure on the ground of the front axle and an increase in the pressure of the rear axle by an amount of 6 to 8 %. Similar results of pressure redistribution between the axles of wheeled running systems in the presence of traction load from a working machine are noted in studies (Patil, 2015;Renčín et al, 2017). Analysis of completed studies (Polcar et al, 2017;Patil, 2015;Renčín et al, 2017) allows concluding that if there is a traction resistance of a working machine on the tractor hook, the front axle of the tractor is unloaded and the load of the rear axle increases.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Experimental studies of changes in the soil response from changes in the traction load on the hook of a wheeled tractor (Polcar et al, 2017) showed that with the traction resistance of the working tool in the range from 55 kPa to 70 kPa, there is a decrease in the pressure on the ground of the front axle and an increase in the pressure of the rear axle by an amount of 6 to 8 %. Similar results of pressure redistribution between the axles of wheeled running systems in the presence of traction load from a working machine are noted in studies (Patil, 2015;Renčín et al, 2017). Analysis of completed studies (Polcar et al, 2017;Patil, 2015;Renčín et al, 2017) allows concluding that if there is a traction resistance of a working machine on the tractor hook, the front axle of the tractor is unloaded and the load of the rear axle increases.…”
Section: Introductionsupporting
confidence: 59%
“…Similar results of pressure redistribution between the axles of wheeled running systems in the presence of traction load from a working machine are noted in studies (Patil, 2015;Renčín et al, 2017). Analysis of completed studies (Polcar et al, 2017;Patil, 2015;Renčín et al, 2017) allows concluding that if there is a traction resistance of a working machine on the tractor hook, the front axle of the tractor is unloaded and the load of the rear axle increases.…”
Section: Introductionsupporting
confidence: 59%
“…A second option for developing a direct model of the tire-rim interaction was to simulate it through a FEM model of the entire wheel, where information about the contact pressure distribution on the tire-rim interface [20]- [22] was sought. However, this approach was affected by many limitations, since accurate information on the design of the tire were not available [23], [24]. Even nowadays, tire structure modelling and analysis represent a challenging operation as non-linearity occurs in the material properties as well as in the contact boundary conditions.…”
Section: Experimental Modelmentioning
confidence: 99%
“…Tire–road contact pressure distribution testing methods include pressure cell, triaxial load pin, piezoelectric sensor, and pressure-sensitive film [ 29 , 30 , 31 ]. The accuracy of tire grounding characteristic measurements is affected by the sensors’ size, spacing, and sensitivity between the tire and the ground.…”
Section: Introductionmentioning
confidence: 99%